THE EFFECT OF WALKING EXERCISE PROGRAM (WEP) TO DECREASE CANCER RELATED FATIGUE (CRF) IN CHILDREN WITH LEUKEMIA - Dini Maulinda; Angga Arfina; Eka Malfasari (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
Cancer Related Fatigue (CRF) in children with leukemia is one of the complaints that is often experienced due to the effects of chemotherapy. One of the actions that can be done to reduce it is through the Walking Exercise Program (WEP). WEP is a program exercise developed based on the principles of frequency, duration, intensity, and activity. The purpose of this study was to determine the effect of physical exercise WEP on fatigue in children with leukemia with the design "Quasy Experimental Pretest-Posttest without control ”. The population of this study were all children with leukemia in YKAKI Riau with a total sample of 30 respondents by considering inclusion and exclusion criteria. The data analysis used was univariate and bivariate analysis with the test Wilcoxon to compare fatigue between before and after the intervention. The results showed that the average fatigue of children with leukemia before getting intervention was 3.53 (SD 2.763; 95% CI 2.50-4.57) and the average fatigue of children with leukemia after receiving intervention was 1.23 (SD 1.104; 95% CI.82) -1.65). Based on the results of the test analysis Wilcoxon , the value was significance 0.000 (p <0.05), thus there was a significant difference in fatigue between before the intervention and after the intervention was given. The recommendation from the results of this study is that WEP can be used as an intervention in providing nursing care to children with leukemia to reduce fatigue.